The Sosialisasi Pengolahan Limbah Rumah Tangga Untuk Pupuk Cair Pada Dawis Gajah Birowo KEL Mangunharjo Kec Tembalang Kota Semarang - ambarsari, arum; Septiono, Aris; Pahlevi, Muhammad Reza (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Waste management in the Dawis Gajahbirowo area, Mnagunharjo Village, Tembalang District, Semarang City, which has been carried out so far, is only sorting organic and non-organic waste. Non-organic waste such as paper and plastic has been collected and sold to waste collectors, while organic waste has not been further managed. This dive the organic waste is collected and taken to the Final Shelter to be taken to the final disposal site by garbage trucks that are present once a week and often not scheduled on a regular basis. This causes the appearance of a foul smell from the household waste. Socialization of household waste treatment is one of the alternative solutions to reduce bad odors as well as to increase the value of the benefits of household waste. This socialization rowed in conjunction with the Semarang City government's program in strengthening the food security of residents, one of which is that residents are required to plant chili and aloevera. It is hoped that the results of this household waste management can be used to water the plants, thereby reducing the residents' budget to buy fertilizer.